The Protective Role Antioxidant of Vitamin C in the Prevention of oral Disease: A Scoping Review of Current Literature - Rosa, Alessio; Pujia, Alberto Maria; Arcuri, Claudio (European Journal of Dentistry, 2024)
This review meticulously examined the connection between vitamin C and periodontal disease, as well as the potential of vitamin C to prevent this condition. To gather relevant data, comprehensive electronic searches were conducted across various databases, including PubMed, EMBASE, Cochrane Library, and Web of Science, focusing on studies that explored the relationship between vitamin C and periodontal disease in individuals aged between 18 and above. From an initial pool of 421 articles, 14 were ultimately chosen for detailed analysis. This selection encompassed seven cross-sectional studies, two case–control studies, two cohort studies, and three randomized controlled trials. The analysis of these studies revealed a consistent negative association between vitamin C intake, as well as its levels in the blood, and the incidence of periodontal disease across all seven cross-sectional studies. This indicates that higher vitamin C intake and blood levels are linked to a decreased risk of developing periodontal disease. In the two case–control studies, individuals suffering from periodontitis were found to have both a lower intake of vitamin C and reduced levels of vitamin C in their blood compared to those without the disease, further underscoring the potential protective role of vitamin C against periodontal disease. The progression of periodontal disease was observed to be more rapid in patients with lower dietary intake or blood levels of vitamin C compared to controls. Regarding the effects of vitamin C administration as an intervention, there was an improvement noted in gingival bleeding among patients with gingivitis; however, no significant benefits were observed in cases of periodontitis, specifically concerning alveolar bone absorption. Through the meticulous examination of available studies, this systematic review underscores the notion that adequate vitamin C intake and maintaining sufficient levels of vitamin C in the blood can contribute significantly to reducing the risk of periodontal disease.
Keywords: vitamin C; periodontal disease; nutrition; oral health; tooth